2004
DOI: 10.1111/j.1440-1827.2004.01659.x
|View full text |Cite
|
Sign up to set email alerts
|

Chorionic plate vessels as an origin of amniotic fluid neutrophils

Abstract: The present study was conducted to investigate the potential anatomical source of amniotic fluid neutrophils. Microdissection of neutrophils from the chorioamnion of the fetal membranes and the amnion of the chorionic plates of 10 preterm placentas with acute chorioamnionitis was performed and the genotypes of the neutrophils were compared with those of the mother and fetus using polymerase chain reaction of nine autosomal STR loci. In separate analyses, we reviewed eight cases of fetal autopsies with increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Indeed, a previous report implied that neutrophils migrate from the fetal vasculature of the chorionic plate (i.e. chorionic vasculitis) into the amniotic cavity 51 , particularly in those cases without acute umbilical phlebitis or arteritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a previous report implied that neutrophils migrate from the fetal vasculature of the chorionic plate (i.e. chorionic vasculitis) into the amniotic cavity 51 , particularly in those cases without acute umbilical phlebitis or arteritis.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, experimental evidence showed that amniotic fluid neutrophils from women 49 or rhesus monkeys 50 undergoing preterm labor were of fetal origin. In such cases, these innate immune cells could originate from the fetal vessels of the chorionic plate 51 . However, abundant neutrophils have also been observed in the amniotic fluid of women with a severe maternal inflammatory response without a fetal inflammatory response in the placenta 13, 46 , indicating that further research is required to investigate whether, amniotic fluid neutrophils are of maternal origin or a mixture of both fetal and maternal neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…Cells within the placenta, amniotic membranes, and uterus can all participate in the innate immune response, secreting cytokines and chemokines including IL-8, IL-10, monocyte chemoattractant protein-1, and regulated on activation, normal T-expressed and presumably secreted (RANTES) (6,25). In addition, fetus-derived neutrophils can occupy the amniotic fluid in chorioamnionitis (18). Although we have shown the fetal lung can directly respond to endotoxin, the contribution of cells in the uterus, placenta, and amniotic membranes could alter how the fetal innate immune system responds to both microbial products and inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42][43][44][45][46][47][48] Neutrophils are the most abundant leukocytes in the amniotic fluid in cases of intra-amniotic infection. 19 These innate immune cells seem to be fetal 49 and originate from the chorionic plate; 50 yet, further evidence is required to prove their fetal origin using genetic fingerprinting. Recently, using immunophenotyping, we demonstrated that amniotic fluid neutrophils express proinflammatory cytokines such as tumor necrosis factor-a, macrophage inflammatory protein (MIP)-1a, MIP-1b, interleukin (IL)-1a, IL-1b, and IL-8.…”
Section: Introductionmentioning
confidence: 99%